Exploring Adult Learners Usage of Information Communication Technology during a Virtual Peer Coaching Experience - Ladyshewsky, Rick; Pettapiece, Ronald (OLC, 2015)
The purpose of this study was to explore how post-graduate students in a fully online business course used information communication technology during a virtual peer coaching experience. In this exploration of technology use it was found students required additional guidance in the use of technologies such as email, telephone calling, and more media rich tools such as Skype and Blackboard Collaborate during a virtual peer coaching session. They did not fully understand how to use these different mediums to guide and structure the coaching experience. They were frustrated by the lack of media richness when using tools with low levels of audio-visual connectivity. The findings suggest that the increasing use of technology in education does not necessarily mean that students will use it appropriately, even if they are adept at learning online or use the technology in their daily lives. Therefore, instructors cannot make assumptions about students’ technological literacy even though these same students may appear to have a high level of competency learning online. Guidelines for using ICT in virtual peer coaching are provided as a result of this exploration.